Evaluation of the inhibitory mechanism of Pennisetum glaucum (pearl millet) bioactive compounds for rheumatoid arthritis: an in vitro and computational approach - Sharif, Maria; John, Peter; Bhatti, Attya; Paracha, Rehan Zafar; Majeed, Abid (Frontiers in Pharmacology, 2024)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by synovial infiltration and pannus formation, significantly contributing to the global disability rate with rising incidence. Despite advances in biological drugs, no treatment has successfully cured or averted its progression. Consequently, natural drugs are being explored as alternative therapeutic strategies.Objective: This study aims to evaluate the therapeutic potential of Pennisetum glaucum (Pearl Millet) and identify its bioactive compounds to assess their effectiveness against RA targets. Methods: Therapeutic potential of Pennisetum glaucum extracts was evaluated by antioxidant and antiinflammatory assays. Gas Chromatography-Mass Spectrometry (GC-MS) was utilized to identify the compounds in Pennisetum glaucum extract. The pharmacokinetics and safety profile of these compounds were studied by Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) analysis. Network pharmacology, molecular docking and molecular dynamic (MD) simulation was employed to identify the active compounds and their therapeutic targets in Pennisetum glaucum for RA treatment. Results: Acidified methanol (AM) extract of Pennisetum glaucum showed the highest phenolic (213±0.008 mg GAE/g DW) and flavonoid content (138.1±0.03 mg RE/g DW), demonstrating significant antioxidant and anti-inflammatory potential. GC-MS of AM extract identified 223 compounds. Lipinski and toxicity parameters screened out 17 compounds. Protein-Protein Interaction (PPI) analysis shortlists 20 key targets in RA pathways, nine of which were upregulated in five microarray datasets. Molecular docking and MD simulations have revealed that compound-7 (benzenesulfonamide, 2-nitro-N-phenyl-) and compound-9 (Pregnane-3,20-diamine, (3.beta.,5.alpha.,20S)-) binds strongly with MMP9, JAK2, PTGS2 and HIF1a compared to the reference, predicting stable interaction with these upregulated genes. Finally, PASS (Prediction of Activity Spectra for biological active Substances) analysis further validated the anti-arthritic potential of these compounds based on their chemical structure.This study uncovers the therapeutic drug candidate against HIF1a, MMP9, JAK2 and PTGS2 for RA from Pennisetum glaucum active compounds, laying the groundwork for future studies.